COMMUNICATION PATTERNS BETWEEN DRUG COURIER WITH CUSTOMERS IN SLEMAN DISTRICT - Linggo Widiantoro; Subhan Afifi; Yenni Sri Utami (The Indonesian Journal of Communication Studies, 2017)
Drug trafficking is still happening today. This activity involves dealer, couriers adan users. Communication between couriers and users is increasingly intense when drug dealing transactions are carried out. In a general sense courier is someone who has the responsibility to conduct the exchange of goods between two or more people. The purpose of this research is to find out how they interact with users. Thus, a qualitative research requires observation in the field to obtain enough data to make conclusions. About the results of research, researcher founded that illegal drugs courier used communication symbols that are only understood by them and their communities. The drug courier profile has a staggering illicit in addition to being couriers, they also as a student. Research also found they use direct and indirect communication pattern during transactions.